Assessment of antinociceptive actions of fatty acid amides in pharmacological blockade of PPARα receptors in experimental peripheral neuropathy - Doronkina, Anastasya S.; Zhavoronok, Irina P.; Mikhal’chuk, Alexander L.; Bogdan, Vasily G. (Experimental Biology and Biotechnology, 2023)
The effect of fatty acid amides during the blockade of PPARα nuclear receptors on nociceptive sensitivity and gait parameters in rats with normal and experimental peripheral neuropathy was studied. It was found that in rats with ligation of the sciatic nerve, the introduction of fatty acid amides against the background of PPARα receptor blockade led to a significant decrease in the severity of the nociceptive response to mechanical and thermal stimuli. When registering gait patterns, an increase in the intensity and area of the limb imprint, as well as in limb transfer rate was noted.
Keywords: palmitoylethanolamide; stearoylethanolamide; palmitoylglycinamide; gait patterns; nociception; neuropathy; analgesic effect; fatty acid amides; nuclear receptors